Boundary element method reconstruction of two‐dimensional magnetic‐field maps from measured boundary data in accelerator magnets. Issue 1 (1st January 2019) - Biccioli, Leonardo; Di Rienzo, Luca; Petrone, Carlo; Russenschuck, Stephan
Abstract : Rotating‐coil magnetometers are standard devices for measuring integrated magnetic fields of accelerator magnets. The coil intercepts the magnetic flux at a radius given by the dimensions of the measurement shaft that comprises a set of induction coils. For magnets of a rectangular aperture with a large aspect ratio (larger than 3:1) the cylindrical domain will cover only a portion of the magnet aperture. We, therefore, explore an alternative sampling technique using boundary data acquired from a displaced stretched‐wire or from a translating fluxmeter. The method presented in this study concerns the reconstruction of the two‐dimensional map of the integrated magnetic field distribution in the entire magnet aperture using the measured boundary data.